Analysis of seismic Response and Slope Stability for Intake Tunnel Entrance of Hongyan River Nuclear Project. Issue 4 (September 2019) - Zhao, Jie; Lan, Wenjun; Wang, Guixuan
Abstract: The principle of dynamic analysis of Flac3D, setting of boundary condition and the solving method of dynamic safety factor for slope are introduced in this article firstly, and the three-dimensional finite difference model of the portal of intake tunnel is built by Flac3D which uses the nonlinear dynamic analytical method to simulate response regularity of the portal of intake tunnel and the high slope backfilled here under seismic load for Hongyan River nuclear intake tunnel first-stage project in Liaoning province. The corresponding change rule of the internal force of tunnel entrance under the effect of running safe seismic load SL1 and ultimate safe seismic load SL2 is gotten by time-histories changing curve under the effect of different seismic and the comparison of tunnel lining internal force diagram; the location sliding surface and dynamic safety factor time-histories curve of the high slope backfilled at the tunnel entrance are gotten by building two-dimension finite element model and doing stability analysis under seismic. Analysis result shows that for tunnel entrance, the analysis method and conclusions of the seismic weak position of the tunnel portal are the sidewall and getting the location of sliding surface and minimum dynamic safety factor time-histories curve of high slope. For similar nuclear power intake tunnel project, the conclusion can be a reference and have a certain reference value for the seismic design of tunnel.